Morphological and morphometric studie of the buffaloes muscle fibers - de Lima Francisco, Caroline [UNESP] (2010)
The aim of the study was to evaluate the muscle fiber types of Longissimus dorsi (LD) and Semitendinosus (ST) muscles of 28 Mediterranean buffaloes not-castrated and its possible modulation according with the different slaughter weights (450, 480, 510 and 540 kg). Samples of the muscles were collected and submitted the electrophoresis (SDS-PAGE), m- ATPase and NADH-TR techniques. The relative percentage of isoforms MyHC were measured, as well as, frequency, area and diameter of muscle fiber types. The absence of MyHC IIb isoform in Mediterranean buffaloes was evidenced, which had only three MyHC isoforms (IIa, IIx/d and I), whose percentage had not varied significantly (P > 0.05) between the slaughter weights. The presence of hybrid fibers (IIA/X) in muscles LD and ST allowed to the classification of the fiber types for a contraction activity, in fast and slow. For both muscles, the frequency was higher for fiber fast in all the evaluated categories; however had differences (P < 0.05) in the frequency of muscle fiber types LD and ST in the slaughter weights evaluated. The animals of slaughter weight 540 kg showed higher values for area and diameter of the fibers, as much for the LD as well as the ST. It is necessary to execute more works with the buffalo species to evidence the characteristics of the muscular development in diverse situations (breeding systems) so that, thus, the manipulations for the man in the breeding of these animals are carried through in efficient way.